Pengaruh Produk, Harga, Distribusi Terhadap Volume Penjualan Produk Nabati Pada PT. Pinus Merah Abadi - M Davin; Sri Retnaning Rahayu; Jati Imantoro (Jurnal Manajemen DIVERSIFIKASI, 2025)
Based on field findings, the issue identified is the fluctuation, which tends to decrease, in thesales volume of PT Pinus Merah Abadi. The objective of this study is to determine the impactof product, price, and distribution on the sales volume of Nabati products at PT Pinus MerahAbadi. This study is a quantitative research, using an explanatory research type, with timeseries data from July 2022 to May 2023, and analyzed using multiple linear regression. Theresults show that price has a positive effect on the sales volume at PT Pinus Merah Abadi.Product has a positive effect on the sales volume at PT Pinus Merah Abadi. Distribution hasa positive effect on the sales volume at PT Pinus Merah Abadi. Price, product, anddistribution together have a positive effect on the sales volume at PT Pinus Merah Abadi,with the most significant variable being price.